How to have narrative‐flipping history in a pandemic: Views of/from Latin America. (27th July 2020) - Birn, Anne‐Emanuelle
Abstract: This piece seeks to elucidate how and why Latin America is neither anecdotal nor peripheral to pandemic preoccupations—nor to larger health and disease narratives—past and present. First, it examines the world's proportionately most destructive pandemic as coterminous with the rise of imperialism. Next, it traces how the impetus for international health cooperation based on regional crises predated and informed efforts elsewhere. Finally, it explores two under‐charted narratives: the creative harnessing of data produced under adversity, and alternative health solidarities that bypass reigning hierarchies of "humanitarian" aid. Together, these glimpses underscore a fundamental need for incorporating histories of and from Latin America to overcome the "history‐telling injustice" created by the centuries‐long Western dismissal of knowledge, practices, experiences, and existential meaning generated in the Global South. In short, these accounts provide a more complex and possibility‐filled restructuring of dominant narratives around the diverse trajectories and consequences, as well as varieties of resistance, that shape understandings of pandemics.